Avaliação da satisfação do usuário em relação ao catálogo on-line da Biblioteca do Instituto Nacional de Pesquisas da Amazônia - INPA - Cardoso, Caio Silva (Brasil, 2019)
In the information retrieval and retrieval process, there are numerous tools for the composition of this action, among which is the public access collective catalog (OPAC), online catalog or simply online catalogs. It is of paramount importance to the participation of the tool to assist the user, namely, what the library has and will be able to recover what it looks for even in external points of the information unit. The main objective of this study is to verify if the online catalog of the INPA Library is supplying the informational needs of its users. The research is configured as a field study, of a qualitative nature, having as a universe the users of the Library of the National Institute of Research of the Amazon (INPA) located in the city of Manaus and as a sample had 101 participants of the research as total population constituted by the non-probabilistic accidental sample. The data collection instrument was determined by an online questionnaire used through the Google Forms Platform and after an email interview with the information unit librarians to validate the responses. From the analysis, it was found that the tool of search and retrieval of information according to the indicators used to compose the data collection instrument that most of the questions are found to be contributing positively. In conclusion, the INPA Library's online catalog is satisfying the informational needs of its real users, although the automation process is not yet completed, however, the purpose of the tool is fulfilling its commitment.